Synthesis and characterization of MnO–ZnO/AC adsorbents for adsorptive removal of HS from natural gas - Jiao J Zhang; Wen Y Wang; Li P Shen; Guo J Wang; Hua Song (Adsorption Science & Technology)
Adsorbents consisting of Mn x O y , Zn x O y , and Mn x O y –Zn x O y supported on activated carbon (AC) have been successfully prepared and characterized by X-ray photoelectron spectroscopy (XPS), X-ray diffraction analysis (XRD), Fourier-transform infrared spectroscopy (FTIR), specific surface area (BET) and SEM. The results show that Mn is present in the forms of Mn 3+ and Mn 4+ , and Zn is present in the form of Zn 2+ . Mn and Zn mainly exist in the forms of MnO 2 and ZnO respectively, as the active components of the adsorbents. MnO 2 –ZnO/AC was found to exhibit the best H 2 S desulfurization performance. At 313 K, the breakthrough time was 108 min, the saturated sulfur capacity was 334.7 mg/g, and the degree of desulfurization was 74.2%. The H 2 S removal capacities of the different adsorbents decreased in the order: MnO 2 –ZnO/AC > ZnO/AC > MnO 2 /AC > AC. The MnO 2 –ZnO/AC adsorbent retained some activity for removal of H 2 S after regeneration at 643 K for 2 h in air.